Human Resource Competencies, Organizational Culture, and Employee Performance - Dian Indiyati; Astri Ghina; Adelia Farhani Romadhona (GoAcademica Research & Publishing, 2021)
The performance of an employee plays an essential role in an organization because it contributes to the achievement of the performance of every organizational function. Several previous studies showed that human resource competencies and organizational culture can affect employee performance. This study aimed to test and analyze the competencies of human resources and organizational culture on employee performance at Bio Farma both partially or simultaneously. This study was conducted using a quantitative method. Data collection techniques using a questionnaire distributed to employees of Bio Farma with samples taken of 300 employees. The research results were tested using path analysis. The results show that human resource competencies and organizational culture had a significant effect on employee performance at Bio Farma, either partially or simultaneously.